Arauchemus, a new spider genus of the Echemus group (Araneae: Gnaphosidae: Echeminae) from Araucaria Forest areas in southern Brazil, with notes on habitat preferences and phenology - Ott, Ricardo; Brescovit, Antonio Domingos (Zootaxa, 2012)
The new genus Arauchemus is proposed to include two new species from southern Brazil. Arauchemus graudo sp. nov. andArauchemus miudo sp. nov. are described from São Francisco de Paula in the state of Rio Grande do Sul, Brazil. Both sympat-ric species were sampled along 20 months at three different habitats: primary and secondary forests and at Pinus silvicultures.A. graudo sp. nov. and A. miudo sp. nov. presented larger numbers at primary and secondary forests respectively. Both speciespresented stenochronic male activity patterns with male activity peak between the end of summer and beginning of autumn. Morphometric data on male cephalothorax indicate large size overlapping of both species.